2010
DOI: 10.1111/j.1749-6632.2009.05301.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of proinflammatory cytokines in the generation and maintenance of joint pain

Abstract: The proinflammatory cytokines tumor necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6) not only promote and maintain inflammation, they also contribute to the generation and maintenance of inflammatory pain by acting at nociceptive nerve cells. A large proportion of dorsal root ganglion (DRG) neurons express TNF receptors and receptor units for stimulation with IL-6. In the rat model of antigen-induced arthritis (AIA), neutralization of TNF-alpha by etanercept and infliximab reduced inflammation-evoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 55 publications
4
123
0
1
Order By: Relevance
“…Proinflammatory cytokines like tumor necrosis factor (TNF) and interleukin 6 (IL‐6) are both of specific importance in RA pathogenesis, and specific cytokine blockade has been shown beneficial 22, 23. Both TNF and IL‐6 also affect pain thresholds in experimental arthritis 24, 25, as well as long‐term sensitization of joint nociceptors 26. In RA, general hyperalgesia to mechanical and thermal stimuli have been reported 27, and decreased pain thresholds over nonpainful areas were also shown in established RA, but not in early disease, suggesting the impact of long‐term inflammation in this context 28.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines like tumor necrosis factor (TNF) and interleukin 6 (IL‐6) are both of specific importance in RA pathogenesis, and specific cytokine blockade has been shown beneficial 22, 23. Both TNF and IL‐6 also affect pain thresholds in experimental arthritis 24, 25, as well as long‐term sensitization of joint nociceptors 26. In RA, general hyperalgesia to mechanical and thermal stimuli have been reported 27, and decreased pain thresholds over nonpainful areas were also shown in established RA, but not in early disease, suggesting the impact of long‐term inflammation in this context 28.…”
Section: Discussionmentioning
confidence: 99%
“…29 IL-6 not only promotes and maintains inflammation in arthritis but also contributes to the generation and maintenance of inflammatory pain by acting at nociceptive nerve cells. 30 In a clinical study, anti-IL-6R antibody (tocilizumab) has been shown to be a novel therapeutic strategy for certain inflammatory and autoimmune diseases, including RA and systemic onset juvenile idiopathic arthritis, with significant clinical improvement and amelioration of joint damage. 31 Some studies have demonstrated that uric acid crystals can induce human eosinophils and neutrophils to produce the neutrophil chemokine CXCL8.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that macrophages produce a number of inflammatory cytokines, particularly interleukin (IL)-1b, IL-6 and tumour necrosis factor (TNF)-a, which contribute to pain and the progression of OA [8][9][10]. In addition, Hill et al [11] used magnetic resonance imaging (MRI) imaging to demonstrate that synovitis correlates with OA pain.…”
Section: Introductionmentioning
confidence: 99%